PENGARUH SIKAP, KONTROL PERILAKU DAN KOMITMEN PROFESIONAL TERHADAP NIAT MELAKUKAN WHISTLEBLOWING (Studi Kasus Pegawai Badan Keuangan Daerah Kabupaten Karanganyar) - Fetika Kurniawati; Muhammad Abdul Aris (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
In the modern era, there are still many frauds in various business activities, one of which is in companies. Therefore, it is necessary to report fraud ( whistleblowing) to minimize fraud in the company. There are several factors that influence individual actions to carry out whistleblowing , namely attitude factors, behavioral control and professional commitment. The purpose of this study was to determine the effect of attitude, behavioral control and professional commitment on whistleblowing. The method of determining the sample is non-probability sampling with type of purposive sampling. This study uses multiple linear regression analysis. The results of the study show that attitudes, behavioral control and professional commitment have a positive effect on whistleblowing intentions. This means that the higher the attitude, behavioral control and professional commitment, the higher the accountant's intention to do whistleblowing.